2020
DOI: 10.3390/cells9010106
|View full text |Cite
|
Sign up to set email alerts
|

Is Autophagy Involved in Pepper Fruit Ripening?

Abstract: Autophagy is a universal self-degradation process involved in the removal and recycling of cellular constituents and organelles; however, little is known about its possible role in fruit ripening, in which the oxidation of lipids and proteins and changes in the metabolism of different cellular organelles occur. In this work, we analyzed several markers of autophagy in two critical maturation stages of pepper (Capsicum annuum L.) fruits where variations due to ripening become clearly visible. Using two commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
0
13
1
1
Order By: Relevance
“…In climacteric fruits the reduction of photosynthetic capacity during ripening is coupled with the burst of aerobic metabolism, whose energy balance is more favorable. To our knowledge, the only publications showing increasing expression of autophagy genes with ripening has been made in non-climacteric fruits such as pepper, grapevine, and the present one made in strawberry (Ghan et al, 2017;López-Vidal et al, 2020). This brings the questions of whether autophagy is a relevant process during ripening of climacteric fruits.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In climacteric fruits the reduction of photosynthetic capacity during ripening is coupled with the burst of aerobic metabolism, whose energy balance is more favorable. To our knowledge, the only publications showing increasing expression of autophagy genes with ripening has been made in non-climacteric fruits such as pepper, grapevine, and the present one made in strawberry (Ghan et al, 2017;López-Vidal et al, 2020). This brings the questions of whether autophagy is a relevant process during ripening of climacteric fruits.…”
Section: Discussionmentioning
confidence: 77%
“…Transcriptomic analyses on grape berry skin revealed that a set of ATG genes (ATG18g, ATG9, ATG11, and ATG2) showed a higher expression concomitant with ripening, supporting a role for autophagy in fruit senescence (Ghan et al, 2017). A recent study, analyzing autophagy related genes and proteins (ATG8, ATG4, ATG5, ATG9, and NBR1), and confirming the presence of autophagic-like structures, suggested that autophagy occurs during ripening in pepper (López-Vidal et al, 2020). However, the importance of autophagy during fruit ripening has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 90%
“…However, depending on the sulphate availability in the soil, the nature of the sulphur-mobile molecules mobilized through the autophagy-dependent remobilization process is different. In line with the role of autophagy in nutrient remobilization, the study by Lopez-Vidal et al [ 9 ] confirms the role of autophagy in metabolic changes occurring during pepper fruit ripening and reveals its implication in the recycling of organelles in this crop. The work by Tarnowski et al [ 10 ] focuses on the role of the selective autophagy cargo receptor NBR1.…”
mentioning
confidence: 67%
“…For example, rice mutants defective in autophagy showed sporophytic male sterility and immature pollen ( Kurusu and Kuchitsu, 2017 ). Ripened pepper fruits exhibited increases in the expression of ATG4 , ATG8a , and ATG9 ( Lopez-Vidal et al, 2020 ), and postharvest fruit senescence of Ziziphus jujube was delayed by the inhibition of autophagy ( Deng et al, 2019 ). Constitutive overexpression of ATG5 or ATG7 increased seed yields and the levels of fatty acids in Arabidopsis seeds ( Minina et al, 2018 ), suggesting that upregulated autophagy has a positive effect on increasing crop fitness and oil accumulation in the breeding of high-yield oil crops ( Ortiz et al, 2020 ).…”
Section: Agricultural Applicationsmentioning
confidence: 99%